Collagen Gentamicin for Prevention of Sternal Wound Infection: Effective or Not? - Friberg, Örjan; Bodin, Lennart (The Thoracic and Cardiovascular Surgeon, 2013)
Background Prophylactic local application of collagen-gentamicin sponges for prevention of sternal wound infections (SWI) after cardiac surgery has been used routinely in risk patients for several years at our center. However, a recent US study failed to show a significant reduction in SWI with the prophylaxis. Therefore, a systematic reevaluation of the effect of local collagen gentamicin was conducted.Methods A complete follow-up of all cardiac surgery patients 2 months postoperatively was achieved. All SWIs were recorded. The effect of the prophylaxis was analyzed, and differences in risk factors were compensated for using multiple logistic regression analyses and Coarsened Exact Matching (CEM).Results A total of 950 patients were included. Established risk factors for SWI were confirmed. The use of collagen-gentamicin prophylaxis was independently associated with a highly significant reduction in SWI (odds ratio [OR] = 0.30, 95% confidence interval = 0.16 to 0.57; p < 0.001). Applying the more advanced statistical method, CEM indicated that the effect of the prophylaxis may be even greater.Conclusions The use of local collagen-gentamicin prophylaxis was associated with an approximately 70% reduction in the rate of SWI compared with standard intravenous antibiotic prophylaxis alone.
Keywords: wound infection; statistics; wound healing; surgery; complications